An Australian Contribution to International Trade Theory: The Dependent Economy Model1. Issue 298 (7th June 2016) - Metaxas, Phillip Edmund; Weber, Ernst Juerg
Abstract : The dependent economy model is also known as the 'Australian model' and the 'Salter–Swan–Corden–Dornbusch model' but neither title adequately conveys the scope and sequence of contributions that were instrumental to its development. In this paper attention is given to indispensable contributions made by the Australian public servant Roland Wilson and the British economist James Meade. The model's development is placed in the broader context of the evolution of balance of payments theory, and the paper highlights a vital Australian contribution to international trade theory, namely, the identification of the real exchange rate as the critical relative price in balance of payments adjustment.